Transformation of Kulcapi Use in Karo Society Traditions in Medan: A Study on Style, Genre, and Social Function - Yerikho Delvinci Ginting; Yosua Saputra Ginting; Wahyu Perdana Tarigan; Prima Nopraka Tarigan; Ryandi Ginting; Mauly Purba (Mahesa Research Center (PT. Mahesa Global Publishing), 2024)
The kulcapi is a traditional musical instrument deeply embedded in Karo cultural practices. This study aims to trace its historical usage within traditional ceremonies and rituals, examine its functional evolution from ancient times to the modern era, and analyze its transformation from a ritualistic to an entertainment medium. Employing a historical approach, this research utilizes literature review and case studies related to the kulcapi's role within Karo culture. Findings indicate that the kulcapi has experienced a significant functional transformation: initially a solo instrument in ritual contexts, it became an integral part of the gendang telu sedalanen ensemble and has more recently merged with modern instruments, such as the keyboard. This transition reflects the kulcapi's adaptation to social and cultural changes while presenting challenges to its traditional values. The study concludes that preserving and developing the cultural heritage associated with the kulcapi is essential for maintaining Karo cultural identity amidst global modernization pressures.